Piperidinium surfactants functionalized with carbamate fragment: Aggregation, antimicrobial activity and cytotoxicity - Kushnazarova, Rushana A.; Mirgorodskaya, Alla B.; Kuznetsov, Denis M.; Vasilieva, Elmira A.; Amerhanova, Syumbelya K.; Voloshina, Alexandra D.; Zakharova, Lucia Ya (Biochimica et biophysica acta. General subjects, 2024)
The biomimetic nature of supramolecular systems, the structural similarity of synthetic surfactants to biomolecules (lipids, proteins), provide them with high membranotropy, the ability to overcome biological barriers, and affinity towards biosubstances. Despite rather high toxicity cationic surfactants are of importance as antimicrobial agents, gene nanocarriers and mitochondria targeted ligands. To minimize this limitation, cationic amphiphilic matrix undergoes modification with various functional groups. In this work, new piperidinium cationic surfactants containing one or two carbamate fragments were prepared; their aggregation behavior was systematically studied by tensiometery, spectrophotometry and fluorimetry. The presence of a carbamate fragment leads to a 2-3-fold decrease in critical micelle concentration and to a significant increase in solubilization capacity compared to unsubstituted analogue. Evaluation of the antimicrobial effect showed that all compounds exhibit high bactericidal and fungicidal activity against a wide range of pathogenic microorganisms, including their resistant forms. Importantly, the introducing carbamate moiety allows of decreasing hemolytic activity of cationic surfactants. The data obtained make it possible to recommend carbamate piperidinium surfactants as effective biocompatible and biodegradable nanocontainers for hydrophobic probes with high antimicrobial effect and moderate hemolytic activity.